Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Group Investigation Berbasis ICT Terhadap Kemampuan Komunikasi Peserta Didik Pada Materi Larutan Elektrolit dan Non Elektrolit - Linda Astuti; Sukro Muhab; Zulmanelis Darwis (Jurnal Riset Pendidikan Kimia (JRPK), 2019)
This study aims to determine the effect of the application of cooperative learning models type Group Investigation based ICT on students' communication skills. This research was conducted with quantitative methods. The sampling technique uses purposive sampling. Learning was carried out in one experimental class and one control class by applying cooperative learning models type GI based ICT and non ICT. The research instrument uses statement questions that have been declared valid and reliable. The results of hypothesis testing of two independent samples obtained t stat (2,897)> t table (1,667), so it can be concluded that there is a positive influence on the application of cooperative learning type Group Investigation based ICT on students’ communication skills. Further analysis on each indicator of communication skills, it can be seen that indicators identifying problems, gathering information, and drawing conclusions have a significant influence on the results of the experimental class and the control class. While indicators write summaries and use good grammar and spelling, there is no significant influence between the experimental class and the control class. Keywords Communication Skills, Cooperative Learning Models Type Group Investigation, ICT Based Learning